From poor law society to the welfare state: school meals in Norway 1890s–1950s - Andresen, Astri (BMJ Group, 2007)
This article examines the main trends in the history of publicly organised school meals in Norway, while casting comparative glances at Britain. First, it argues that the status of school meals today is strongly influenced by three intertwined strains of past tradition: poor relief, universal welfare and the ideal of full‐time and nutritionally competent housewives. Second, tradition is also visible in the extent to which publicly organised meals are seen as solutions to problems – in the past to hunger or malnourishment, today to obesity and malnourishment – and not simply as a meal. Third, the creation of civil and health conscious citizens has, to varying degrees, been a part of the school meals programme, as the school itself has had, and continues to have, such an agenda.